2020
DOI: 10.1055/s-0039-1691823
|View full text |Cite
|
Sign up to set email alerts
|

Tractography in Neurosurgery: A Systematic Review of Current Applications

Abstract: The ability to visualize the brain's fiber connections noninvasively in vivo is relatively young compared with other possibilities of functional magnetic resonance imaging. Although many studies showed tractography to be of promising value for neurosurgical care, the implications remain inconclusive. An overview of current applications is presented in this systematic review. A search was conducted for ((“tractography” or “fiber tracking” or “fibre tracking”) and “neurosurgery”) that produced 751 results. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 275 publications
0
19
0
Order By: Relevance
“…Deterministic DTI has been used in routine clinical practice to determine TTD in a validated and user-independent approach with robustness to peritumoral edema (25,32). New techniques such as probabilistic tractography capable of visualizing areas of complex fiber architecture have been investigated, however, these approaches have not yet been established in clinical practice (54). For visualization of the CST, we used deterministic DTI as the established clinical routine.…”
Section: Limitationsmentioning
confidence: 99%
“…Deterministic DTI has been used in routine clinical practice to determine TTD in a validated and user-independent approach with robustness to peritumoral edema (25,32). New techniques such as probabilistic tractography capable of visualizing areas of complex fiber architecture have been investigated, however, these approaches have not yet been established in clinical practice (54). For visualization of the CST, we used deterministic DTI as the established clinical routine.…”
Section: Limitationsmentioning
confidence: 99%
“…However, it has repeatedly been shown that the DTI technique may be prone to errors, particularly in the situation of crossing or kissing fibers or presence of peritumoral edema, among other influencing factors [45,46]. Other sequences and tracking algorithms are developed to become applicable in the clinical setting, yet alternatives to conventional DTI and related analyses are still elaborate and mostly far from routine use [47,48]. Thus, with technical refinements, measurements of LTDs that are even closer to reality may soon become possible.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Third, the technique of DTI has its inherent methodological shortcomings, which could lead to aberrant fiber reconstruction and visualization, particularly for crossing or kissing fibers and in the presence of edema, which is commonly observed in relation to brain tumors [52,53]. Other sequences and tracking algorithms are developed to become applicable in the clinical setting, but good alternatives to conventional DTI and its tractography-based analyses are still not available for clinical routine use [54,55]. Fourth, the tractography maps generated by nTMS-based DTI FT for depiction of the language network need further validation, ideally by intraoperative DES as the gold-standard method.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%